PEMBELAJARAN DEWASA SEBAGAI SUATU JIHAD INTELEKTUAL - Zulkifli Khair, Rosman Md. Yusoff (PERINTIS eJournal, 2021)
The purpose of this paper is to discuss the adult learning from an Islamic perspective, in the context of jihad. Intellectual jihad jihad as a branch of jihad is one of the unique characteristics of adult learning from an Islamic perspective. Even though the writing is generally conceptual, it was offset by the content analysis study of the adult learning process of Imam Syafii by his short biography by Dr. Tariq Suwaidan. Based on the literature, the authors propose three main aspects in the formation of the concept of intellectual jihad; sacrifice in intellectualism and scholarship, for the sake of Allah and to establish the religion of Allah. The concept of 'intellectual jihad' is found in the form of 'adult learning' through the great intellectual, Imam Syafii.